Unlocking the Potential: Analyzing the Impact of Online Games on High School History Education and Learning Outcomes - Chen, Chu; Jenks, Astin (Insan Akademika Publications, 2023)
This research investigates the influence of online games on learning outcomes in high school history subjects, examining their role in engaging students, enhancing critical thinking, and modernizing pedagogy. Employing a mixed-methods approach, the study integrates qualitative interviews with students and teachers and quantitative surveys to provide a comprehensive understanding of the research question. The research findings reveal that online games significantly improve student engagement, motivation, and learning outcomes in history education. Students report increased enthusiasm and participation, and test scores show a statistically significant improvement when online games are integrated into the curriculum. The qualitative data illuminate the positive impact of online games on students' critical thinking skills and the quality of teacher-student interaction. Educators can leverage these findings to modernize pedagogical practices, foster interdisciplinary learning, and create inclusive educational environments that cater to diverse learning styles and abilities. The research contributes to the broader understanding of technology's evolving role in education, emphasizing its potential to bridge past and present, engage digital natives, and prepare students for the complexities of the future. It underscores the transformative power of online games in education, providing a dynamic and interactive approach that resonates with today's learners.